Internet of Things based Accident Prevention and Detection System - Meena, K; Amuthadevi, C; Sai Kumar, G (International Journal of Engineering and Technology, 2018)
Â Recent growth in technology makes our life faster and easier. This development in technologies leads to enhance the traffic hazards. In this paper, Internet of Things based accident prevention and detection system is proposed to deduce accidents and save human life. The vehicle performance has been continuously monitored for safety purposes. This technique is annoying to maintain speed balance to avoid accident and provide safety to the driver. Hence, a novel approach is proposed to avoid accidents and save the victims while accidents occur. Sensors are exploited to give alarm 'ON' when distance between two vehicles is too short. If accident happens, then the camera is automatically turned on and captures the images around 180 degree angles. This emergency alert information including the location is transferred to nearest police station, ambulance service and relatives through GSM modem. The major component of the project includes a Arduino, motion sensor, touch sensors, relay and GSM modem.